Including the phosphorus cycle into the LPJ-GUESS dynamic global vegetation model (v4.1, r10994) – global patterns and temporal trends of N and P primary production limitation - M. Dantas de Paula; M. Forrest; D. Warlind; J. P. Darela Filho; K. Fleischer; A. Rammig; T. Hickler; T. Hickler (Geoscientific Model Development)
Phosphorus (P) is a critical macronutrient for plant growth, often limiting plant production in areas where plant demand is higher than soil supply. In contrast to nitrogen (N), P cannot be sourced from the atmosphere; therefore, where it is rare, it becomes a strong constraint on primary production. Due to this, most dynamic global vegetation models (DGVMs) are incorporating a prognostic P cycle in addition to N, improving their ability to correctly predict stocks and fluxes of carbon and how climate change may impact N and/or P limitations to soil processes and plant productivity.